Understanding Private Sector Antimalarial Distribution Chains: A Cross-Sectional Mixed Methods Study in Six Malaria-Endemic Countries - Palafox, Benjamin (Public Library of Science, 2014)
BACKGROUND: Private for-profit outlets are important treatment sources for malaria in most endemic countries. However, these outlets constitute only the last link in a chain of businesses that includes manufacturers, importers and wholesalers, all of which influence the availability, price and quality of antimalarials patients can access. We present evidence on the composition, characteristics and operation of these distribution chains and of the businesses that comprise them in six endemic countries (Benin, Cambodia, Democratic Republic of Congo, Nigeria, Uganda and Zambia). METHODS AND FINDINGS: We conducted nationally representative surveys of antimalarial wholesalers during 2009–2010 using an innovative sampling approach that captured registered and unregistered distribution channels, complemented by in-depth interviews with a range of stakeholders. Antimalarial distribution chains were pyramidal in shape, with antimalarials passing through a maximum of 4–6 steps between manufacturer and retailer; however, most likely pass through 2–3 steps. Less efficacious non-artemisinin therapies (e.g. chloroquine) dominated weekly sales volumes among African wholesalers, while volumes for more efficacious artemisinin-based combination therapies (ACTs) were many times smaller. ACT sales predominated only in Cambodia. In all countries, consumer demand was the principal consideration when selecting products to stock. Selling prices and reputation were key considerations regarding supplier choice. Business practices varied across countries, with large differences in the proportions of wholesalers offering credit and delivery services to customers, and the types of distribution models adopted by businesses. Regulatory compliance also varied across countries, particularly with respect to licensing. The proportion of wholesalers possessing any up-to-date licence from national regulators was lowest in Benin and Nigeria, where vendors in traditional markets are important antimalarial supply sources. CONCLUSIONS: The structure and characteristics of antimalarial distribution chains vary across countries; therefore, understanding the wholesalers that comprise them should inform efforts aiming to improve access to quality treatment through the private sector.